Fast estimation of adult cerebral blood content and oxygenation with hyperspectral time-resolved near-infrared spectroscopy - Cohen, David Jonathan Fulop; Li, Natalie C.; Ioussoufovitch, Seva; Diop, Mamadou (Frontiers in Neuroscience, 2023)
Near-infrared spectroscopy (NIRS) can measure tissue blood content and oxygenation; however, its use for adult neuromonitoring is challenging due to significant contamination from their thick extracerebral layers (ECL; primarily scalp and skull). This report presents a fast method for accurate estimation of adult cerebral blood content and oxygenation from hyperspectral time resolved NIRS (trNIRS) data. A two-phase fitting method, based on a two-layer head model (ECL and brain), was developed. Phase 1 uses spectral constraints to accurately estimate the baseline blood content and oxygenation in both layers, which are then used by Phase 2 to correct for the ECL contamination of the late-arriving photons. The method was validated using Monte Carlo simulations and subsequently evaluated in a two-layer brain-mimicking phantom. Phase 1 recovered cerebral blood oxygenation and total hemoglobin with an accuracy of 2.7±2.5% and 2.8±1.8%, respectively, with unknown ECL thickness, and 1.5±1.4% and 1.7±1.1% when the ECL thickness was known. Phase 2 recovered these parameters with an accuracy of 1.5±1.5% and 3.1±0.9%, respectively. A fast (0.18 s when using Phase 2 to track changes) method for accurate estimation of adult cerebral blood content and oxygenation from hyperspectral trNIRS measurements was introduced and validated. Future work will include further validation in tissue-mimicking phantoms with various top layer thicknesses and in a pig model of an adult head before human applications.